HALALAN-TOYYIBAN PROCEDURES FOR CHICKEN SLAUGHTERHOUSE IN THE TRADITIONAL MARKETS IN BANDUNG - Salim, Mochamad Agus; Adhi Utama, Akbar (Journal of Business and Management, 2017)
Abstract. The Government has issued Undang-Undang No. 33 Tahun 2014 tentang Jaminan Produk Halal (UU JPH). The essence of the Act is article 4, The Government guarantee that all products circulated and traded in the territory of Indonesia must be "Halal" certified. The issuance of this law is very logical, considering that the majority of Indonesians are Muslim. In Islamic teachings, there are terms "Halal" and "Toyyib" that are one unity. Thus, every things consumed by Muslims should be "Halal" and "Toyyib". Beginning with this, the researcher tried to do research on the concept of "Halal" and "Toyyib" is associated with the theory of Operational Management. In the beginning, the researcher defined â€œHalalan-Toyyibanâ€ Standards in poultry slaughtering. This standards are obtained from a regulation from MUI coupled by 2 regulations from Farming Department of Bandung City. Then, the researcher identified the real condition about chicken slaughtering process and layout in 10 points from 5 traditional markets in Bandung City. The researcher then compared these ideal and real conditions. The researcher found that there gaps between these conditions. Then the researcher analyzed these gaps. The researcher found that the main problem is layout. Based on the problems found above, the researcher proposed a layout as a solution. This layout is developed from "Halalan-Toyyiban" standards before. This layout consist sequence of process. Underneath there is a flow chart as the workersâ€™ instruction. Keywords: Poultry slaughterhouse, chicken slaughtering, poultry slaughtering, layout, process, procedure, Halal, Toyyib